DEMATEL Method in Implementing Green Business Process Management (BPM) in Micro, Small and Medium Enterprises in Kendari City - Manan, La Ode Abdul; Lajaria, Ridha Taurisma; Imran, Imran (International Journal of Finance Research, 2023)
MSMEs are often considered the biggest contributors to environmental damage and produce more waste than other businesses. This is because MSMEs, in general, are still focused on achieving economic performance. Research sampling was carried out using the Slovin formula. The number of samples in this study was 96.68 or 100 IMK as samples. The collected data was analyzed using the DEMATEL method, which is used to analyze cause-and-effect relationships between a set of factors that influence a decision-making process. Based on the results of this research, "green attitude" has the highest interaction and the strongest impact. Improving the behavior of individuals, including managers, customers, and employees of the organization, is a top priority. Environmentally conscious behavior influences environmentally friendly organizational strategies and governance. Environmental knowledge and awareness influence environmentally conscious behavior; this shows that with increasing environmental knowledge and awareness in organizations, environmentally friendly behavior also increases